Utilization of Digital Technology in Arabic Language Learning At MIS Ikhlasiyah Tuamang - Al Fatha, Khairani; Anisa Khairani; M. Billy Kurniawan; Mutiya; Shifa Sofyan; Syahri Anggi Rezeki; Yesi Wulandari; Sapri (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The use of technology in learning Arabic has become the main focus in efforts to increase the effectiveness and attractiveness of learning. This research discusses various approaches and technological applications that can be used to enrich the Arabic language learning experience. Online-based learning methods, use of mobile applications and interactive multimedia platforms are the main aspects explored. Evaluation of learning outcomes shows that technology integration can improve students' understanding of grammar, vocabulary and speaking competence in Arabic. The application of technology in Arabic language learning is expected to make a significant contribution to the progress of language education by utilizing the potential of modern technology. This research aims to determine the use of digital technology in Arabic language learning in class V of MIS Ikhlasiyah Tuamang. The method used is descriptive qualitative. The sample in this study was all class V students of MIS Ikhlasiyah Tuamang. Data collection techniques use observation, interviews and documentation. The data analysis technique uses theories from Milex and Huberman, namely reducing data, presenting data, and concluding data. The results of this research show that there is minimal use of digital technology in Arabic language learning in class V of MIS Ikhlasiyah Tuamang. This is shown from the results of interviews and observations that have been carried out, that in class V MIS Ikhlasiyah Tuamang, Arabic language learning very rarely uses digital technology, teachers more often use Arabic textbooks as a learning medium.